Genome-Wide Association Study and Rare Variant Association Studies of Strabismus in the All of Us Research Program - Kyoung A Viola Lee, MPH; Corey Tesdahl; Inas F. Aboobakar, MD; Ashish Jain, PhD; Mayra Martinez Sanchez, PhD; Kimberly Jin, BA; Isdin Oke, MD; Mary C. Whitman, MD, PhD (Ophthalmology Science)
Objective: Despite significant evidence of a genetic contribution to strabismus, precise genetic mechanisms have not been identified. There are distinct population differences in the prevalence of strabismus and its subtypes. This study aimed to explore the genetic contributions to strabismus in different ancestral groups. Design: Case-control. Participants: The All of Us Research Program includes genotypic and phenotypic data from a diverse population of adults (age ≥18 years at time of enrollment) across the United States. Among participants with whole-genome sequences available, strabismus cases were identified based on diagnosis codes from their electronic health record. Participants with conditions associated with acquired strabismus, such as trauma, thyroid eye disease, tumor, or stroke, were excluded from the case and control cohorts. The final cohort consisted of 1579 cases and 121 490 controls of European (EUR) ancestry, 235 cases and 40 602 controls of Admixed American (AMR) ancestry, and 365 cases and 53 577 controls of African American (AFR) ancestry. Individuals of other ancestral groups were not included due to small numbers of strabismus-affected participants. Methods: Genome-wide association study of common variants (minor allele frequency >1%) and rare variant association study at the gene level for strabismus. Main Outcome Measures: Individual single nucleotide polymorphisms (SNPs) significantly associated with strabismus and genes with significant burden of rare variants in strabismus. Results: Genome-wide association study identified one locus with 3 significant SNPs (rs2247113, rs2667037, and rs2715926) in intron 1 of PLA2R1 in the AFR group, and 2 loci, one in RIMBP2 intron (rs184071225) and one intergenic (rs191788703), in the AMR group. Rare variant association study revealed 33 genes with a statistically significant (P value < 5 x 10-5) increased burden of variants: 9 in the EUR cohort: ZNF468, CMYA5, NSUN4, TEX45, ICAM3, ADAMTS20, FANCI, HLA-DQB1, and GRIN3B; 14 in the AMR cohort: RIMBP1, UCKL1, EHBP1L1, CLTCL1, HELB, TULP2, APOB, SMPD3, OBSCN, NLRP8, PLOD1, NUP214, OR6J1, and NOP10; and 10 in the AFR cohort: C4orf54, PIGG, OR10D3, MKNK1, KNCN, MS4A14, CSN2, BDKRB1, IL1RL1, and ISM2. Conclusions: Genetic associations with strabismus differed between ancestry groups, although genes in similar pathways, such as synaptic signaling and structural muscle proteins, were found in multiple groups. This highlights the importance of including diverse populations in studies of genetic associations and suggests that multiple pathways may lead to strabismus in different population groups. Financial Disclosure(s): Proprietary or commercial disclosure may be found in the Footnotes and Disclosures at the end of this article.